Evaluation of Renal Parenchymal Stiffness in Chronic Kidney Disease Using Shear Wave Elastography - Divakar, A V V Satya; Paulraj, Jenikar; Virmani, Sachin; Yadlapalli, Likitha (Journal of Neonatal Surgery, 2025)
Background: Chronic kidney disease (CKD) is a public health burden worldwide. Conventional imaging does not measure renal stiffness or fibrosis accurately. Shear wave elastography (SWE) is an ultrasound-based non-invasive technique of tissue stiffness measurement that can potentially enhance CKD staging. Purpose: To assess the value of SWE in the measurement of renal parenchymal stiffness in CKD patients and compare it with traditional ultrasound..